The issues with transnational fast moving consumer goods supply chains originating India and South Africa - Kumar, Dinesh (My University, 2013)
The use of transnational supply chains has been perceived as the “mantra for success” in the ear of globalisation, changing customer demographics and demand. The fast-moving customer goods (FMCG) industry has also joined this bandwagon, along with other industries, such as the high-technology industry, in order gain competitive advantage. However, the trade regimes of developing (emerging) economies have played a significant role in establishing the context for the supply chain originating in a particular country, and therefore in containing the foreseen benefits accruing from supply chains becoming a transnational process. This thesis was focused on identifying issues within selected transnational FMCG supply chains origination in India and South Africa. It also identified the steps that supply chain managers were taking to address these issues. It also proposed a framework for supply chain operating model to address the identified issues. The research used a combination of analytical models to investigate the different aspects of the various transnational supply chains. To examine the underlying aspects of the various FMCG supply chains, a typology model in conjunction with an operational model, a financial model and a governance model were used. Supply chain operations reference (SCOR), an operational analytical model, was used extensively on this thesis. Detailed typology and process flow maps specific to transnational FMCG supply chains were also developed. The collective case study approach was used as the research methodology. A total of four cases spanning two countries – India and South Africa – and dealing with two product segments (packaged food and personal care products) were studied. Data for the study was collected thorough primary sources (in multiple face-to-face interviews) and secondary sources (from case-specific documents and reports). After the data was analysed, it was found that the various supply chains in the FMCG industry displayed similar typologies and issues, some of which were unique to each country. The typology of the transnational supply chains for all four cases was very similar in terms of their distribution structure setup, product life cycle, sourcing models combination, customer relations, marketing methods and degree of globalisation. However, in both countries, the supply chain issues identified in the personal care segment, such as product proliferation and supplier unreliability, were different from those identified in the packaged food segment, such as strict food-related regulatory laws and greater manufacturing complexities. Some of the typical issues affecting local supply chains, such as the bullwhip effect and lower supply chain adaptability, were not evident in the transnational supply chains. The steps supply chain managers were taking to address these issues, such as standardising processes and implementing new technology, were found to be similar in all cases. However, in India, supply chain managers were also focusing on government initiatives, establishing contracts with suppliers and customers, and implementing supply chain policies, while in South Africa they were also focusing on improving supply chain skills, improving branding in transnational markets and implementing foreign exchange controls. The overall conclusion was that there was considerable potential for achieving competitive advantage by setting up transnational supply chains, provided that the problems identified within transnational supply chains were adequately addressed by supply chain managers. However, in some scenarios, the steps taken in terms of available best practice models results in further set of issues arising. The identification of the issues facing supply chain managers and the development of a framework of operating model to address the identified issues with transnational FMCG supply chains were the most significant contributions of this research study.
Keywords: Supply chain, FMCG industry, transnational, supply chain managers, India, South Africa.